Los procesos cognitivos básicos y la comprensión lectora en estudiantes de primer ciclo del paralelo “B” de la carrera de Derecho de la Facultad Jurídica, Social y Administrativa de la Universidad Nacional de Loja, 2023-2024. - Ponce Calderón, Junior Stalin (2024)
The present Curricular Integration Work addresses the analysis of the relationship between the Basic Cognitive Processes of Attention and Memory, and the Reading Comprehension levels in students of the first cycle of the “B” parallel of the Law career of the Juridical, Social, and Administrative Faculty, during the academic period 2023-2024. The research follows a quantitative, descriptive, correlational, and transversal approach, with a non-experimental design. Three instruments were used to evaluate the participants: the d2 Test for attention, the Memory Subscale of the RIAS Test for memory, and the ICLAU Instrument for reading comprehension in university students, with a sample of 36 students. The analysis was carried out using Spearman's Linear Correlation Coefficient to establish relationships between the independent and dependent variables. The results revealed an insignificant relationship between direct D2 scores and ICLAU Reading Comprehension total scores (+0.02). Weak correlations were also identified in Hits, Errors, Omissions, Commissions and the ICLAU Levels (Literal, Information Reorganization, Inferential, Critical, and Appreciation), as well as between the RIAS Subscale Memory Index and ICLAU Reading Comprehension total scores (-0.08). Further insignificant correlations were found between Verbal and Nonverbal Memory and the ICLAU Levels (Literal, Information Reorganization, Inferential, and Critical). In conclusion, the null hypothesis is accepted, and the alternating hypothesis of the research is rejected.